Online Shopping Intentions Of Tiktokshop Consumers: The Influence Of Consumer Privacy and Shopping Enjoyment Study in Department Management of Universitas Simalungun - Saragih, Liharman; Ginting, Fauziah Aftitah; Haidir, Sharla Nasyawa; Rahayu, Elwi Sri; Harahap, Dwi Putri Aisyah; Okista, Rizky (ProBisnis : Jurnal Manajemen, 2024)
In this study, researchers made a study entitled "Online Shopping Intentions Of Tiktokshop Consumers: The Influence Of Consumer Privacy On Shopping Enjoyment In E-Commerce". The purpose of this study is to determine the relationship between consumer privacy and shopping satisfaction in TikTokshop E-Commerce Study in Department Management of Universitas Simalungun. This study shows that the shopping_enjoyment (X1) and consumer_privacy (X2) variable can explain its effect on the Enjoyment (Y) variable by 71.6%. The F test show that both variable (shopping_enjoyment, consumer_privacy) can effect simultan to the online_shopping_intention. The T-test show that both of variable have value of 0.00. it means that the shopping_enjoyment (X1) and consumer_privacy (X2) have a significant effect to the online_shopping_intention in tiktok shop